Associação e valor preditivo da classificação WIfI (wound, ischemia, foot infection) com amputação maior e mortalidade - Alessandra Rocha Luz (2020)
ASSOCIATION AND PREDICTIVE VALUE OF THE WIFI (WOUND, ISCHEMIA AND FOOT INFECTION) CLASSIFICATION SYSTEM WITH MAJOR AMPUTATION AND MORTALITY Objective: to verify the association and predictive value of the SVS-WIfI (Wound, Ischemia and foot Infection) Classification System with major amputation and death rates in patients with peripheral arterial disease (PAD) and / or diabetic foot. Material and Methods: a retrospective cohort was conducted at University Hospital Risoleta Tolentino Neves in Belo Horizonte-MG/Brazil in patients with diabetic foot and / or peripheral arterial disease from January 2015 to December 2017 recording clinical history, risk factors and comorbidities, nutritional status, functional mobility, revascularizations, minor and major amputations, and mortality rates. All patients were stratified according to SVS-WIfI classification system and were classified into amputation risk stages: stage 1: very low risk; stage 2: low risk; stage 3: moderate risk; and stage 4: high risk . Results: 660 patients were enrolled at the following risk stages: stage 1 -10.6%; stage 2 - 21.3%; stage 3 - 33.1%; stage 4 - 34.8%. The majority of men (62.9%) had arterial hypertension (84.4%), diabetes mellitus (67.1%) and smoking (61.9%) as predominant risk factors and comorbidities. Two-thirds (67%) of the patients were at nutritional risk (90.5% malnourished or obese). Revascularizations, major amputation and mortality rates increased as the risk stage worsened. The major amputation rate during hospitalization was 17.8% (36% in stage 4); In-hospital mortality rate was 7.1% (10.8% in stage 4). The length of stay increased as the WIfI risk stage worsened. The revascularization rate was 41.2% at the first hospitalization with additional 20.9% during the follow-up (15.1% reinterventions). The average follow-up period was 428.7 days (range 7-1391 days). Functional mobility worsened as WIfI risk stage increased. The highest amputation rate was 26.5%, with a statistical difference between risk stages 4 and risk stages 1, with 5.7% for risk stages 1 (OR 0.149; CI 0.053 - 0.414) and 46% for risk stages 4 (OR 4.472; CI 3.103 - 6.445). The longest amputation-free survival was 64.3%, of which 85.7% for risk stages 1 (OR 3.699; CI 1.856 - 7.372) and 46.5% for risk stage 4 (OR 0.306; CI 0.219 - 0.429 ). The mortality rate was 15.9%, with 8.5% for risk stages 1 (OR 0.465; CI 0.196 - 1.103) and 21.7% for risk stages 4 (OR 1.894; CI 1.242 - 2.889).The Receiver operating characteristic (ROC) curves demonstrated that the stage risk 4 had sensitivity of 60.57% (95% CI; 52-67.9) and specificity of 74.43% (95% CI 70.3-78.3) in predicting major amputations. Conclusions: in patients with chronic limb threatening due to peripheral arterial disease and diabetic foot, the WIfI classification is associated with major amputation and mortality. As the WIfI risk stage worsened, it was associated with higher amputation and mortality rates and also with the clinical, laboratory, nutritional and functional mobility worsening. The WIfI risk stage 4 has high specificity and sensitivity in predicting major amputation. The reported major amputation and mortality rates were similar to those of the international centers of excellence.